Polymers blends and their effects on the mechanical behavior and physical properties of prolonged release tablets prepared by direct compression - Al-Enazy, Fouaz Kayem (2009)
In this study, physical mixtures of selected formulations of Theophylline, diltiazem HCI and Diclofenac sodium using a blend of kollidon SR, carnauba wax and ethylcellulose were prepared first and then subsequently tabletted by direct compression process under different compression forces namely, 5, 10, 15 and 20 Kn. The tablet weight was fixed in each formula at 201 mg containing 50 mg drug and 150 mg polymer or blend of polymer and 1 mg magnesium stearate as lubricant.
Thesis (M. Sc. Pharmaceutics)-- college of pharmacy, King Saud University, 2009.
Includes bibliographical references.
Text in English, abstracts in Arabic and english.
Keywords: Drug development; Polymers -- Effectiveness; Mechanical property